2007
DOI: 10.3102/0002831207308645
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Transformation: Cultural and Gender Identity Negotiation in First-Generation Vietnamese Youth

Abstract: This article explores the various ways in which recent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 98 publications
2
29
0
Order By: Relevance
“…Education has an esteemed position within the Vietnamese society. Learning and teaching in Vietnam is highly structured and centrally regulated (Stritikus & Nguyen, 2007).…”
Section: Vietnam From the Perspective Of Cultural Valuesmentioning
confidence: 99%
“…Education has an esteemed position within the Vietnamese society. Learning and teaching in Vietnam is highly structured and centrally regulated (Stritikus & Nguyen, 2007).…”
Section: Vietnam From the Perspective Of Cultural Valuesmentioning
confidence: 99%
“…A small qualitative study of gender identity development among recently immigrated Vietnamese American high school students reported that these youths' culture and gender identity formation was complex and dynamic (Stritikus & Nguyen, 2007). The youth constructed their own gender identities, which fit with their particular social contexts, strategically adopting elements of Vietnamese and mainstream American cultural norms in a process described as "selective acculturation," which was different across genders.…”
Section: Specific Cultural Issuesmentioning
confidence: 99%
“…Goldstein's participants' use of Cantonese in a Canadian high school, which was not legitimated by the school policies, could be considered a means of constructing and investing in peer social capital in order to achieve academic success and meet social needs. Stritikus and Nguyen (2007) maintained that to better understand how immigrant students adapt to the host school culture, it is necessary to account for their gender identity interpretation. They studied the transitions of 30 Vietnamese immigrant students to American schooling and the ways in which they formed cultural and gender identities.…”
Section: Social Adaptation and Negotiation Of Cultures And Identitiesmentioning
confidence: 99%